Succession to the Throne in the Golden Horde: Replacement of the Batuids by the Tuqai-Timurids - I.M. Mirgaleev (Золотоордынское обозрение)
Research objectives: To find out both the principle of succession to the throne in the Golden Horde after the extinction of Batuid family – the ruling dynasty line of the Jochids – and the reasons for the rise of the Tuqai-Timurids. Research materials: In his analysis, the author is based on the genealogical sources and compares them with the Arab-Persian historical works and chronicles. Results and novelty of the research: After the death of Berdibek, the principle of succession in the Golden Horde was disrupted since the Batuid family ceased to exist. The remaining Jochid families had to decide whose line will have had the right to sovereignty. The Time of Troubles of the 1360–70s ended with a Tuqai-Timurid Tokhtamysh’s victory. Replacement of the Batuids by the Tuqai-Timurids was in effect only during the reign of khan Tokhtamysh and therefore it can not be regarded as definitive and generally accepted solution to the problem. In addition to the Tuqai-Timurids, also representatives of the Shibanids will have become khans in the Turko-Tatar yurts in the future. It was precisely the process of disintegration of the Golden Horde and the unsolved problem of succession that led to the fact that hereinafter “any” Jochid could lay claim to the throne in post-Golden Horde yurts.